Newcastle Disease Virus: A Journey from an Avian Pathogen to an Efficient Oncolytic Virus - Shay Tayeb; Amos Panet; Zichria Zakay-Rones (Recent Developments in Chemistry and Biochemistry Research Vol. 11, 2025)
Oncolytic viruses have been extensively studied for decades. Until today, several oncolytic viruses were examined for their anti-cancer effect both as monotherapy as well as in combinations. In this chapter, Newcastle Disease Virus (NDV), which is a major avian pathogen that causes minimal to no symptoms in humans, was discussed. The virus shows an extremely high safety profile as well as potential efficacy in treating various lymphomas and solid tumors, including metastasis. This was shown in several cancerous indications with extensive both preclinical as well as clinical trials. The book chapter discusses the use of different NDV strains as well as the development of an ex-vivo model using fresh human cancerous tissues, which optimizes treatment parameters for clinical trials. This model aims to better understand NDV’s tissue tropism, infection mechanisms, and innate immune responses in human cancers compared to other traditional preclinical models. The use of this model also allows even to compare different viruses for different cancer tissues in order to choose the most efficient virus for specific cancers and even specific patients. In addition, advances in genetic engineering and combination therapies with NDV have shown promising results in enhancing its safety, efficacy, and anti-tumor immune responses, emphasizing its importance as a potential cancer treatment. NDV showed highly efficient capabilities to serve as an anti-cancer vehicle, both as monotherapy as well as in combinations. Yet additional preclinical as well as clinical trials are important for applying the best outcome for different cancer indications in choosing the right modality for using NDV.